1987
DOI: 10.1073/pnas.84.21.7585
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone production and perception in European corn borer moths is determined by both autosomal and sex-linked genes

Abstract: Inheritance patterns for sex pheromone production in females, pheromone detection on male antennal olfactory receptor cells, and male pheromone behavioral responses were studied in pheromonally distinct populations of European corn borers from New York State. Gas chromatographic analyses of pheromone glands, single sensiflum recordings, and flight tunnel behavioral analyses were carried out on progeny from reciprocal crosses, as well as on progeny from subsequent F2 and maternal and paternal backcrosses. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
216
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 14 publications
6
216
3
Order By: Relevance
“…Hybrid females produce intermediate blend ratios of approximately 35:65 Z/E (Roelofs et al 1985;Glover et al 1991), and hybrid male moths preferentially fly to blends of the E/Z isomers in the flight tunnel, although more hybrid males of either E×Z or Z×E crosses fly to the Z blend alone than to the E blend alone. Despite of the fact that natural hybridization between the E and Z pheromone races is well documented in the field, an in-depth genetic analysis of sex pheromone production and perception in this species predicts that no self-sustaining population of hybrids can exist (Roelofs et al 1987). Therefore, the origin of the stable blend-responding populations of P. anxia is intriguing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid females produce intermediate blend ratios of approximately 35:65 Z/E (Roelofs et al 1985;Glover et al 1991), and hybrid male moths preferentially fly to blends of the E/Z isomers in the flight tunnel, although more hybrid males of either E×Z or Z×E crosses fly to the Z blend alone than to the E blend alone. Despite of the fact that natural hybridization between the E and Z pheromone races is well documented in the field, an in-depth genetic analysis of sex pheromone production and perception in this species predicts that no self-sustaining population of hybrids can exist (Roelofs et al 1987). Therefore, the origin of the stable blend-responding populations of P. anxia is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Roelofs et al (1987) speculated that a few simple genetic substitutions could result in the E strain evolving from the Z strain. However, changes in the sex pheromone production system would have to evolve by a different mechanism in P. anxia because the raw materials are not synthesized de novo.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 13 female hybrids discovered via gas chromatographc analysis, 10 were further analyzed for TPI phenotype, and all 10 had the Tpi-l phenotype as expected if their fathers were BE males. Roelofs et al (1987) and Glover et al (1990) also investigated the response profiles of F, males and demonstrated that hybrid males respond to a wide-range of pheromone blends with significant numbers responding to all blends except the E pheromone. In fact, in the more recent study (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the occurrence of species-assortative behaviour is relatively common, in comparison, only a few studies have looked at what developmental mechanism mediates it and, if so, then often only in one of the sexes (fish: Engeszer et al 2004;Verzijden and ten Cate 2007;songbirds: ten Cate and Vos 1999;Slagsvold et al 2002;Hansen and Slagsvold 2003;Riebel 2003; corn borer moths: Roelofs et al 1987;crickets: Shaw 2000;Ritchie 2000; fruit flies: overview in Coyne and Orr 2004). As a consequence, our understanding of the possible evolutionary trajectories leading to assortative behaviour and reproductive isolation is limited.…”
Section: Introductionmentioning
confidence: 99%